2011
DOI: 10.1155/2011/132627
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Handheld Assays for the Detection of Ricin and Staphylococcal Enterotoxin B in Disinfected Waters

Abstract: Development of a rapid field test is needed capable of determining if field supplies of water are safe to drink by the warfighter during a military operation. The present study sought to assess the effectiveness of handheld assays (HHAs) in detecting ricin and Staphylococcal Enterotoxin B (SEB) in water. Performance of HHAs was evaluated in formulated tap water with and without chlorine, reverse osmosis water (RO) with chlorine, and RO with bromine. Each matrix was prepared, spiked with ricin or SEB at multipl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2012
2012
2015
2015

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 7 publications
0
9
0
Order By: Relevance
“…The equations for the dissociation of Tl 2 SO 4 into Tl + cation and SO 4 2-anion when dissolved in water are shown (eqs 1-3), and the formula for the stability constant of TlSO 4 -, β 1 is given (eq 4).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The equations for the dissociation of Tl 2 SO 4 into Tl + cation and SO 4 2-anion when dissolved in water are shown (eqs 1-3), and the formula for the stability constant of TlSO 4 -, β 1 is given (eq 4).…”
Section: Discussionmentioning
confidence: 99%
“…A prior study found that evidence for the existence of the ion TlSO 4 -in solution was inconclusive. 5 Glaser gives the stability constant, β 1 for the formation of TlSO 4 -in 2 M aqueous sodium perchlorate solution as 2.2, 6 and states that Tl + is only weakly hydrated in aqueous solution, and has a low tendency to form complexes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…14-20 Both PCR and catalytic activity assays are indirect methods for detecting ricin. PCR only detects nucleic materials from the plant origin of the toxin, and therefore is not applicable to detect purified ricin, 21, 22 while catalytic activity assays lack specificity towards ricin, since the catalytic activity of all RIPs are similar.…”
Section: Introductionmentioning
confidence: 99%
“…[10,11] Current point-of-care detection technologies use antibodies as the capture agent. [12,13] Antibodies are generally generated from immunized animals, and production and separation of ultrapure biomaterials in large quantities can be expensive. [14] Most antibodies require refrigeration, which can be a major concern if immunoassays are to be used in remote areas, where stability without refrigeration is desired.…”
Section: Introductionmentioning
confidence: 99%